The right thing conscience, profit and personal responsibility in today's business - Seglin, Jeffrey L. (Spiro Press, 2003)
Ethics policies and life in the corporation with an emphasis on hiring, bosses, privacy, lying, cheating and stealing, and leading by example.
Keywords: Business ethics; Business ethics -- Case studies; Wirtschaftsethik; Fallstudiensammlung